Decreasing the Value of Women’s Testimony Compared to Men; A Comparative Study on (Q. 2:282)’s Exegesis Focusing on al-Manār, al-Mīzān, and Min Waḥy al-Qurʾān - sayed mahmood tayebhoseini; Ali Muhammad Hakimian; Muhammad Hassan Shirzad; Muhammad Hussein Shirzad (پژوهش‌های تفسیر تطبیقی, 2022)
Received: 2021/10/17  |   Correction: 2021/12/4   |   Accepted: 2022/2/19It seems (Q. 2:282) to be one of the Qur’anic verses that, in its transition process to the modern period, has brought to mind a kind of gender discrimination between men and women, according to which the value of women’s testimony has been halved compared to men. Many Qur’anic exegetes, willingly or unwillingly, have suggested readings based on gender presuppositions against women, claiming their suffering from some negative human attributes such as lack of intellect, poor memory, and inability to record events. These readings were considerably popular until the beginning of the 14th/ 20th century. However, in the transition to the modern period and the rise of contemporary emerging questions, socio-cultural contexts have been provided to distance oneself from interpretive traditions and propound up-to-date readings of this verse. Taking a comparative approach, the present research thus attempts to study the different possibilities for the interpretation of the verse in question, focusing on three modern Qur’anic exegeses, namely al-Manār, al-Mīzān, and Min Waḥy al-Qurʾān. It shows that the exegetes of the mentioned interpretations have tried to offer some new understandings of the (Q. 2:282), appropriate to modern questions and contemporary needs, of course, through taking three different ways.* Tayebhoseini, S.M; Hakimian, A.M; Shirzad, M.H; Shirzad, M.H. (2022) Decreasing the Value of Women’s Testimony Compared to Men; A Comparative Study on (Q. 2:282)’s Exegesis Focusing on al-Manār, al-Mīzān, and Min Waḥy al-Qurʾān. Biannual Journal of Comparative Exegetical Researches, 8 (15) 113-138. Doi: 10.22091/PTT.2022.6789.1955.